A new decomposition of open and closed sets in topological spaces - Granados, Carlos (2021)
In this paper, we show some properties on *b-open sets. Besides, we introduce the notions of generalized *b-closed sets, locally *b-closed sets, regular generalized *b-closed sets and weakly *b-closed sets. Moreover, we study some of their properties.